Assessment of the Factors That Hinder Male Involvement in Maternal Health in Kasangati Town Council - Peace Nepilu Agunyo (Uganda Christian University, 2025)
The Kasangati Town Council study looked into the barriers to male participation in maternal health. The following goals served as the study's guidelines: To determine whether sociocultural norms prevent men from participating in maternal health at Kasangati Health Center IV, Kasangatii Town Council; whether ignorance prevents men from participating in maternal health at Kasangati Health Center IV, Kasangatii Town Council; and whether educational attainment prevents men from participating in maternal health at Kasangati Health Center IV, Kasangatii Town Council. Both qualitative and quantitative methods were used in the study's modified descriptive research design. According to the study, cultural beliefs in the community have a significant influence on how pregnant women feed their babies. This suggests that even though the men would want to provide their expectant mothers with a healthy, balanced diet, some foods are forbidden in their society, even though they are nutritious. The obstacles to male participation in maternal health at Kasangati Health Center IV would also be removed by raising knowledge of men's involvement in reproductive health, family planning initiatives, and reproductive health decision-making. The study concluded that there was still a lack of knowledge regarding family planning programs, men's involvement in reproductive health, and men's role in reproductive health decision-making. Raising awareness is therefore necessary to remove the obstacles that prevent men from participating in maternal health in Kasangati Health Center IV and the entire Wakiso area.
THESIS